2018
DOI: 10.1063/1.5020239
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic observation of lateral and vertical charge transportation in Si nanocrystals sandwiched by amorphous SiC layers

Abstract: Charge injection and transportation process is a fundamental problem to Si nanocrystals (Si-ncs) based electric and photonic devices. In the manuscript, a single layer of Si-ncs sandwiched by amorphous Si carbide (a-SiC) was prepared by excimer laser annealing of a-SiC/a-Si/a-SiC multilayers, and the charging effect was then characterized by Kelvin probe force microscopy (KPFM) on the microscopic scale. Opposite charges were injected into Si-ncs through the biased tip and formed a core-ring or up-down shaped d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Although the dual‐pass scan might introduce a problem of charge exchange between the tip and sample during the first pass, Li et al recently proved that the problem can be effectively avoided by increasing the ratio of setpoint amplitude ( A sp ) to the tip free amplitude ( A 0 ) . The ratio A sp / A 0 was set as 0.8 in the first pass of our KPFM measurement, which has been demonstrated to block the tip‐sample charge exchange successfully in our previous work . On the other hand, the FM‐KPFM detects the electrostatic force gradient and thus is expected to have a better resolution than AM mode, however, it suffers a reduced bias sensitivity and usually requires a high AC voltage ( V AC > 2 V) .…”
Section: Methodsmentioning
confidence: 91%
“…Although the dual‐pass scan might introduce a problem of charge exchange between the tip and sample during the first pass, Li et al recently proved that the problem can be effectively avoided by increasing the ratio of setpoint amplitude ( A sp ) to the tip free amplitude ( A 0 ) . The ratio A sp / A 0 was set as 0.8 in the first pass of our KPFM measurement, which has been demonstrated to block the tip‐sample charge exchange successfully in our previous work . On the other hand, the FM‐KPFM detects the electrostatic force gradient and thus is expected to have a better resolution than AM mode, however, it suffers a reduced bias sensitivity and usually requires a high AC voltage ( V AC > 2 V) .…”
Section: Methodsmentioning
confidence: 91%
“…The retention behavior (i.e., potential change after charge injection) was monitored by customized SKPM with a lock‐in amplifier (Model: SR830, Stanford Research) . In a SKPM measurement, an AFM tip was mechanically resonated with a frequency of ≈75 kHz, and an AC bias was applied to the tip with a frequency of ≈17 kHz and a root‐mean‐square voltage of 2 V.…”
Section: Methodsmentioning
confidence: 99%
“…The charge trapping and retention behaviors of nanomaterials have also been studied by EFM/KPFM, such as isolated germanium nanoislands, [ 63 ] individual few‐layer graphene (FLG) films, [ 101 ] Ti 3 C 2 nanosheets, [ 76 ] individual silicon nanoparticles, [ 69 ] Co granular films, [ 48 ] silicon nanocrystals, [ 64,77 ] silicon nanocrystals embedded in SiO 2 film, [ 49–51 ] silicon quantum dots, [ 109 ] P‐doped Si quantum dots, [ 65 ] and Co nanoclusters embedded in SiO 2 . [ 110 ] Verdaguer et al injected charges in isolated graphene sheets deposited on a SiO 2 /Si wafer by KPFM and investigated the discharge process at different relative humidity (RH) conditions.…”
Section: The Properties Of Trapping Charges For Different Materials Bmentioning
confidence: 99%
“…In the past decade, EFM/KPFM has been successfully used to study the injection and retention of trapped charges in inorganic films, [ 16,25,45,46,52–57 ] polymer electrets, [ 47,58–60 ] organic small molecules, [ 42,44 ] the composition of polymer and organic semiconductors, [ 27,41,43 ] nanostructure, [ 48–51,61–78 ] double‐barrier CeO 2 /Si/CeO 2 /Si structures, [ 79 ] DNA molecules, [ 39–80 ] and thin‐film transistors. [ 81–86 ] For example, Heim et al proved that EFM is a useful technique to study the electronic properties of an organic monolayer island at the nanometer scale and found that both carriers are delocalized over the whole island in crystalline monolayer islands, while carriers stay localized at their injection point on a disordered monolayer.…”
Section: Introductionmentioning
confidence: 99%